Justifying the use of excessive force: A critical discourse analysis of Chinese police individual wechat subscription accounts - Wang, Han (Modern Asian Studies)
This article examines how individual police officers in China interpret and justify the use of excessive force on social media through their WeChat Subscription Accounts (WSAs). Existing research examines how the police department uses social media to justify deadly force, but overlooks individual officers$1 (Bonline justifications. Adopting a critical discourse analysis approach, this study analyses 211 articles commenting on a prominent case of police violence in China. The findings shed light on the online voice of Chinese frontline officers, revealing an ideology that defends the use of excessive force. The articles published in WSAs displayed strong empathy towards the involved officer; contested the characterization of the incident as police brutality by police officials, the public, and the media; and employed various strategies to justify the officer$1 (Bs actions. The discussion section expands on these findings by drawing comparisons to justifications in the United States, emphasizing the distinctive dynamic between individual officers$1 (Bonline expression and official police discourse in China, and offering insights for scholars examining online expression and digital nationalism in the Chinese context.- Reproduced s